POLICY TO COMBAT RELIGIOUS EXTREMISM AND TERRORISM IN UZBEKISTAN - Gulxayo Ibodullayeva Shuxrat qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract. This article provides a systematic analysis of Uzbekistan’s policy in combating religious extremism and terrorism. It covers the theoretical foundations of these phenomena, the factors of their origin, and threats to global security. Legal, institutional, and spiritual-educational measures implemented in the country will also be reviewed. Issues of international cooperation will also be analyzed, and scientific and practical proposals for existing problems and their elimination will be put forward.